A flame retardant and anti-drip nylon material and its preparation method and application

Through polymerization, POSS-(NH2)8 and phosphorus flame retardant salt are combined with nylon salt to form a chemical bonded flame retardant and molten droplet-resistant nylon material, which solves the problem that nylon material is prone to molten droplets during combustion, achieves efficient flame retardant and molten droplet-resistant properties, and simplifies the preparation process.

CN119192564BActive Publication Date: 2025-04-22新兴际华(上海)工程科技研究院有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411707151.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-22
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing nylon materials are prone to melt droplets when burned, and their flame retardant droplet resistance is insufficient, and their processing technology is cumbersome and their energy consumption is high.

Method used

Through polymerization, POSS-(NH2)8 and phosphorus flame retardant salt are combined with nylon salt to form a chemical bonded flame retardant and molten droplet nylon material, solving the problems of small molecules migration and viscosity reduction.

Benefits of technology

It realizes the efficient flame retardant and droplet resistance of nylon materials, while simplifying the preparation process and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192564B_ABST
    Figure CN119192564B_ABST
Patent Text Reader

Abstract

The present invention discloses a flame retardant and anti-melting drip nylon material and its preparation method and application. The flame retardant and anti-melting drip nylon material provided by the present invention is obtained by polymerization reaction of POSS flame retardant and anti-melting drip salt, phosphorus flame retardant salt and nylon salt. The present invention introduces a phosphorus and silicon flame retardant and anti-melting drip system containing rich active groups into the main chain of nylon macromolecules by polymerization means, and the flame retardant and anti-melting drip component is connected to the nylon matrix through chemical bonds, which solves the migration problem of small molecular components; the silicon-based flame retardant and anti-melting drip component containing multiple active amino groups can form branched nylon macromolecules, which can solve the reduction of nylon viscosity caused by the introduction of flame retardant monomers and improve the anti-melting drip performance of nylon materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nylon functional modification, and in particular relates to a flame retardant and anti-drip nylon material and a preparation method and application thereof. Background Art

[0002] Polyamide (nylon), as a high-strength, wear-resistant and well-processable polymer material, is widely used in textiles and clothing, transportation, electronics and electrical appliances, etc. However, its inherent flammable and fusible droplet defects limit its application in some special fields.

[0003] The characteristic of nylon materials that they are prone to produce droplets when burning is mainly determined by their linear polymer structure and low viscosity at high temperatures. There are three common methods for modifying nylon materials to make them flame retardant and droplet resistant, namely surface modification, blending modification and copolymerization modification. Among them, surface modification is mainly applied to nylon fibers or fabrics, and the surface of the material is coated or grafted with a flame retardant finishing agent. Its advantages are simple methods and low equipment requirements. However, since the flame retardant only adheres to the surface of the material, there are problems of low fastness and insufficient flame retardant efficiency. Moreover, this method can generally only be used for sheet-like flexible materials such as fabrics or membranes, which has great limitations. Blending modification mainly involves melt blending the nylon matrix with the modifying additives through a twin screw, and the modifier is embedded in the nylon matrix in the form of physical dispersion. The functional durability of the material is generally higher than that of surface modification. However, blending modification is prone to uneven dispersion of the modifier and subsequent migration of small molecules. The copolymerization modification method is to directly connect the modifier to the nylon molecular chain through a chemical bond, solving the problem of flame retardancy and droplet resistance from the intrinsic nature of the material. The materials prepared by the copolymerization modification method have high fastness, no serious problem of small molecule migration, and high flame retardant efficiency. It is an ideal nylon modification method.

[0004] In the related research on nylon modified polymerization, the use of green flame retardants containing halogen-free flame retardant elements such as phosphorus, nitrogen, and silicon is the current mainstream of development. Among them, phosphorus flame retardants have higher flame retardant efficiency, but phosphorus-containing flame retardants generally have poor heat resistance, which can easily reduce the thermal stability of the matrix, resulting in poor anti-melting droplet performance of flame retardant materials. Silicon-based flame retardants mainly achieve physical barriers to flames and oxygen by generating a dense silicon layer during combustion. Although its flame retardant performance is weaker than that of phosphorus-containing flame retardants, the dense ceramic layer generated by its degradation can effectively resist molten droplets. Octaamino cage-type polysilsesquioxane (POSS-(NH2)8) is composed of a silicon-oxygen cage-like inorganic core connected alternately by Si-O and a group R containing an active amino group connected to the Si atom at the top corner of the inorganic core. The Si-O skeleton core of POSS-(NH2)8 can inhibit the chain movement of polymer molecules, thereby giving the nylon matrix good thermal stability and flame retardancy; in addition, the R groups containing multiple active amino groups enable grafting or polymerization reactions between POSS-(NH2)8 and polymer materials, resulting in chemical bonding between the two, achieving uniform dispersion on the molecular layer and improving the performance of molecular materials.

[0005] At present, the main problems of polymer-modified flame-retardant and anti-drip nylon are as follows: first, the flame-retardant and anti-drip effect of a single halogen-free flame retardant element is limited, and it is necessary to explore a suitable flame-retardant and anti-drip compound system; second, the flame retardant has fewer active sites. For example, in patent CN116179075A, the silicon-based flame retardant used has only one active site, which is equivalent to a capping agent and can only be polymerized to the end group of the molecular chain. Adding a large amount will seriously affect the molecular weight and reduce the viscosity of the matrix; the silicon-based flame retardant used in CN107189061A has two active sites and can be polymerized to the nylon main chain, but its reaction activity is low, and it is necessary to prepare esterified nylon, which has high energy consumption and cumbersome processes.

[0006] In summary, the existing flame retardant and anti-drip technology mainly has the following problems: 1. The fastness or migration problem of flame retardant and anti-drip additives; 2. The problem that it is difficult to have both anti-drip performance and flame retardant performance; 3. The problem of complicated processing technology and high energy consumption. Summary of the invention

[0007] The purpose of the present invention is to provide a flame retardant and anti-melting dripping nylon material, which has both high flame retardant efficiency and good anti-melting dripping effect. At the same time, the obtained material has good anti-precipitation performance, and the preparation process is simple and the energy consumption is low.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a flame retardant and anti-drip nylon material, which is obtained by polymerization reaction of POSS flame retardant and anti-drip salt, phosphorus flame retardant salt and nylon salt.

[0010] The present invention introduces a phosphorus and silicon flame retardant and anti-melting dripping system containing rich active groups into the main chain of nylon macromolecules by means of polymerization. The flame retardant and anti-melting dripping components are connected to the nylon matrix through chemical bonds, thereby solving the problem of migration of small molecular components. The silicon-based flame retardant and anti-melting dripping components containing multiple active amino groups can form branched nylon macromolecules, thereby solving the problem of reduced nylon viscosity caused by the introduction of flame retardant monomers.

[0011] The present invention explores a reasonable ratio range of phosphorus and silicon flame retardant components through systematic experiments. The molar ratio of the POSS flame retardant anti-drip salt, the phosphorus flame retardant salt and the nylon salt is (3-10): (5-15): 100; preferably (3-5): (5-10): 100.

[0012] In the present invention, the POSS flame retardant and anti-drip salt is obtained by reacting POSS-(NH2)8 with adipic acid in a molar ratio of 1:(2-8), preferably 1:4.

[0013] Wherein, the structure of POSS-(NH2)8 is shown in Formula I:

[0014]

[0015] In formula I, R is an alkane or aromatic hydrocarbon containing an amino group; preferably, R is selected from or .

[0016] In the present invention, the phosphorus flame retardant salt is obtained by reacting a phosphorus flame retardant with a nylon monomer in a molar ratio of 1:(0.5-2). The preferred molar ratio is 1:1.

[0017] Wherein, the phosphorus-based flame retardant is selected from one or more of the following compounds:

[0018]

[0019] Wherein, the nylon monomer is selected from hexamethylenediamine and / or adipic acid.

[0020] In the present invention, the nylon salt is selected from one or more of nylon 66 salt, nylon 6 salt, nylon 56 salt, nylon 46 salt, nylon 610 salt, nylon 1010 salt and nylon 1212 salt.

[0021] In a second aspect, the present invention provides a method for preparing the flame retardant and anti-drip nylon material, comprising the following steps:

[0022] S1, preparing POSS flame retardant anti-drip salt;

[0023] S2, preparing phosphorus flame retardant salt;

[0024] S3, mixing the POSS flame retardant and anti-melting dripping salt, the phosphorus flame retardant salt and the nylon salt, and reacting to obtain the flame retardant and anti-melting dripping nylon material.

[0025] In step S1 and step S2, the solvent used in the reaction is 75%-100% ethanol solution, preferably 95% ethanol solution; the concentration of the precursor solution in the reaction is 40 wt%-90 wt%, preferably 60 wt%; the stirring speed in the reaction is 50-70 rpm, and the stirring time is 30 min-100 min, preferably 40 min.

[0026] The reaction in step S3 is carried out according to the following operation: nylon salt, end-capping agent and water are added to the reactor, wherein the concentration of nylon salt is 50-70wt%, and the amount of end-capping agent is 0.2mol%-1.5mol% of nylon salt; at room temperature, the reactor is first evacuated to vacuum, and then nitrogen is introduced to 0.2MPa, and the air in the reactor is removed repeatedly 3 times; under the stirring condition of 50rpm-70rpm, the temperature is raised to 230°C within 1.5-2h, and then the pressure in the reactor is maintained at 1.7-1.9MPa by pressure relief, balanced for 20min, then heated to 280°C, and then slowly released to normal pressure, phosphorus flame retardant salt and POSS flame retardant anti-melting salt are added, stirring is continued for 30min, and then vacuumed to below 65Pa, and the material is discharged after stopping the balance for 10min. Among them, air should be avoided from contacting the reaction system during feeding, and nitrogen pressurization can be used for feeding; the stirring speed is appropriately increased to 70rpm-100rpm during feeding.

[0027] Specifically, the end-capping agent can be selected from adipic acid, acetic acid, and p-iodobenzoic acid, and adipic acid can be preferably used here. The concentration of the nylon salt can be preferably 65wt%. The amount of the end-capping agent can be 0.4mol% of the nylon salt. The stirring rate after the nitrogen is introduced can be preferably 60rpm, and the stirring rate can be 80rpm when adding phosphorus flame retardant salt and POSS flame retardant anti-melting salt. The time to rise to 230°C can be preferably 2h. The pressure in the stabilization stage in the kettle can be preferably 1.75MPa.

[0028] In a third aspect, the present invention provides a fabric made from the flame retardant and anti-drip nylon material.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention adopts a polymerization modification method to introduce phosphorus and silicon flame retardant components containing rich active groups into the main chain of nylon macromolecules, so that the modified material has good anti-precipitation performance; the silicon-based flame retardant component used is a polyamino cage-like oligomeric silsesquioxane POSS-(NH2)8 containing multiple active amino groups, which generates a dense silicon layer during combustion to achieve physical barrier to flame and oxygen, thereby playing a flame retardant and anti-melting dripping role; at the same time, the present invention confirms the reasonable ratio range of phosphorus and silicon flame retardant components. Compared with the flame retardant system of a single flame retardant element, it can give nylon materials a higher flame retardant efficiency while achieving an anti-melting dripping effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 These are pictures of the sample strips of the comparative examples and embodiments of the present invention after UL-94 testing, from right to left they are comparative examples 1-4, and embodiments 1-4. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0034] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0035] Taking nylon 66 salt as an example, the preparation method of the flame retardant and anti-drip nylon material provided by the present invention comprises the following steps:

[0036] ① Preparation of phosphorus flame retardant salt:

[0037] A phosphorus-based flame retardant containing an active carboxyl group (or amino group) and a nylon monomer hexamethylenediamine (or adipic acid) are added to a 95% ethanol solution at a molar ratio of 1:1 to prepare a 60wt% flame retardant salt precursor solution. The two solutions are fully mixed and reacted at a stirring rate of 50-70rpm. The active phosphorus-based flame retardant reacts with the nylon monomer to form a salt. During the reaction, the solution temperature rises and crystals precipitate. Stirring is continued for 40 minutes. After sufficient cooling, the solution is filtered and washed with ethanol for 2 to 3 times. The solution is naturally dried or dried at 60°C to obtain a phosphorus flame retardant salt.

[0038] The active carboxyl phosphorus-containing flame retardant involved in the above process may have, but is not limited to, the following structure:

[0039]

[0040] The active aminophosphorus flame retardant involved in the above process may have, but is not limited to, the following structure:

[0041] .

[0042] ②Preparation of POSS flame retardant and anti-drip salt:

[0043] POSS-(NH2)8 and adipic acid are dissolved in a molar ratio of 1:4, respectively, and added into 95% ethanol solution to prepare a 60wt% flame retardant salt precursor solution. Under stirring conditions at a stirring rate of 50-70rpm, POSS-(NH2)8 and adipic acid react to form salts. During the reaction, the solution temperature rises and crystals precipitate. Stirring is continued for 40 minutes. After sufficient cooling, it is filtered and washed with ethanol for 2 to 3 times. It is naturally dried or dried at 60°C to obtain POSS flame retardant and anti-dripping salt.

[0044] The structure of POSS-(NH2)8 involved in the above process is as follows:

[0045]

[0046] The organic branched chain R is characterized by an alkane or aromatic hydrocarbon containing an amino group, and the specific structure may be but is not limited to the following two:

[0047] .

[0048] ③Polymerization of flame retardant and anti-drip nylon materials

[0049] Nylon 66 salt and end-capping agent are mixed with deionized water in a certain proportion and added into a polymerization reactor, wherein the concentration of nylon 66 salt is 50-70wt%, and the amount of end-capping agent is 0.2mol%-1.5mol% of nylon 66 salt. The reactor is first evacuated to vacuum at room temperature, and then nitrogen is introduced to 0.2MPa, and the air in the reactor is removed repeatedly for 3 times. Under the stirring condition of 50rpm-70rpm, the temperature is raised to 230℃ within 1.5-2h, and then the pressure in the kettle is maintained at 1.7-1.9MPa by pressure relief, and balanced for 20min, and then the temperature is raised to 280℃, and then slowly released to normal pressure, and phosphorus flame retardant salt and POSS flame retardant anti-melting salt are added in the proportion of POSS flame retardant anti-melting salt: phosphorus flame retardant salt: nylon 66 salt = x: y: z, x = 3~10, y = 5~15, z = 100. When adding materials, avoid air contact with the reaction system, and nitrogen can be used for pressurized addition. When adding materials, the stirring speed is appropriately increased to 70rpm-100rpm. After the addition is completed, continue stirring for 30min, then evacuate to below 65Pa, stop balancing for 10min and then discharge.

[0050] Example 1

[0051] Preparation of phosphorus flame retardant salt: 3462.7 g (10 mol) of 2-[(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid (DDP) powder as a phosphorus flame retardant component and 1162.1 g (10 mol) of hexamethylenediamine were added to a 95% ethanol solution to prepare a 60wt% flame retardant salt precursor solution. The two solutions were fully mixed and reacted at a stirring rate of 60 rpm. The active phosphorus flame retardant reacted with the nylon monomer to form a salt. During the reaction, the solution temperature increased, and after crystals precipitated, stirring was continued for 40 minutes. After sufficient cooling, the solution was filtered and washed with ethanol three times, and naturally dried to obtain the phosphorus flame retardant salt.

[0052] Preparation of POSS flame retardant and anti-dripping salt: POSS-(NH2)8 (1101.9 g, 1.25 mol) and adipic acid (730.7 g, 5 mol) were added to 95% ethanol solution respectively to prepare a 60wt% flame retardant salt precursor solution. The two solutions were fully mixed and reacted under stirring conditions at a stirring rate of 50-70rpm. POSS-(NH2)8 and adipic acid reacted to form salt. During the reaction, the solution temperature increased and crystals precipitated. Stirring was continued for 40 minutes. After sufficient cooling, it was filtered and washed with ethanol 3 times. It was naturally dried to obtain POSS flame retardant and anti-dripping salt.

[0053] The organic branched chain R of POSS-(NH2)8 involved in the above process is: .

[0054] The stirring rate during the above process was 60 rpm.

[0055] Polymerization of flame retardant and anti-melting nylon material: 2623.5g (10 mol) of nylon 66 salt and end-capping agent adipic acid were mixed with deionized water and added to the polymerization reactor, wherein the concentration of nylon 66 salt was 65wt% and the amount of end-capping agent was 0.4mol% of nylon 66 salt. The reactor was first evacuated to vacuum at room temperature, and then nitrogen was introduced to 0.2MPa, and the air in the reactor was removed repeatedly for 3 times. Under the stirring condition of 60rpm, the temperature was raised to 230℃ within 2h, and then the pressure in the reactor was maintained at 1.75MPa by pressure relief, balanced for 20min, and then the temperature was raised to 280℃, and then slowly released to normal pressure, and phosphorus flame retardant salt and POSS flame retardant anti-melting salt were added according to the ratio of POSS flame retardant anti-melting salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=3, y=5, z=100. Air should be avoided from contacting the reaction system when adding materials, and nitrogen pressurization can be used for feeding. When adding materials, the stirring speed is increased from appropriate to 80 rpm. After the addition is completed, stirring is continued for 30 minutes, and then the vacuum is evacuated to below 65 Pa. The material is discharged after stopping the balance for 10 minutes.

[0056] Example 2

[0057] The difference between it and Example 1 is that POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=3, y=10, z=100, and the other conditions are the same as in Example 1.

[0058] Example 3

[0059] The difference between it and Example 1 is that POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=5, y=5, z=100, and the other conditions are the same as in Example 1.

[0060] Example 4

[0061] The difference between it and Example 3 is that POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=5, y=10, z=100, and the other conditions are the same as those in Example 3.

[0062] Comparative Example 1

[0063] Preparation of phosphorus flame retardant salt: 3462.7 g (10 mol) of 2-[(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid (DDP) powder as a phosphorus flame retardant component and 1162.1 g (10 mol) of hexamethylenediamine were added to a 95% ethanol solution to prepare a 60wt% flame retardant salt precursor solution. The two solutions were fully mixed and reacted at a stirring rate of 60 rpm. The active phosphorus flame retardant reacted with the nylon monomer to form a salt. During the reaction, the solution temperature increased, and after crystals precipitated, stirring was continued for 40 minutes. After sufficient cooling, the solution was filtered and washed with ethanol three times, and naturally dried to obtain the phosphorus flame retardant salt.

[0064] Polymerization of flame retardant and anti-melting nylon material: 2623.5g (10 mol) of nylon 66 salt and end-capping agent adipic acid were mixed with deionized water and added to the polymerization reactor, wherein the concentration of nylon 66 salt was 65wt%, and the amount of end-capping agent was 0.4mol% of nylon 66 salt. The reactor was first evacuated to vacuum at room temperature, and then nitrogen was introduced to 0.2MPa, and the air in the reactor was removed repeatedly for 3 times. Under the stirring condition of 60rpm, the temperature was raised to 230℃ within 2h, and then the pressure in the reactor was maintained at 1.75MPa by pressure relief, balanced for 20min, and then the temperature was raised to 280℃, and then slowly released to normal pressure, and phosphorus flame retardant salt and POSS flame retardant anti-melting salt were added according to the ratio of POSS flame retardant anti-melting salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=0, y=5, z=100. When adding materials, air should be avoided from contacting the reaction system, and nitrogen pressurization can be used for feeding. When adding materials, the stirring speed is increased from appropriate to 80 rpm. After the addition is completed, stirring is continued for 30 minutes, and then the vacuum is evacuated to below 65 Pa. The material is discharged after stopping the balance for 10 minutes.

[0065] Comparative Example 2

[0066] The difference between this comparative example and comparative example 1 is that the POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt in its formula = x:y:z, x=0, y=10, z=100, and the rest is the same as comparative example 1.

[0067] Comparative Example 3

[0068] The difference between this comparative example and comparative example 2 is that the POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt in its formula = x:y:z, x=0, y=15, z=100, and the rest is the same as comparative example 2.

[0069] Comparative Example 4

[0070] Preparation of phosphorus flame retardant salt: same as Comparative Example 1.

[0071] Preparation of POSS flame retardant and anti-dripping salt: POSS-(NH2)8 (1101.9 g, 1.25 mol) and adipic acid (730.7 g, 5 mol) were respectively added to 95% ethanol solution to prepare a 60wt% flame retardant salt precursor solution. The two solutions were fully mixed and reacted under stirring conditions at a stirring rate of 60rpm. POSS-(NH2)8 and adipic acid reacted to form salts. During the reaction, the solution temperature increased and crystals precipitated. Stirring was continued for 40 minutes. After sufficient cooling, it was filtered and washed with ethanol 3 times. It was naturally dried to obtain POSS flame retardant and anti-dripping salt.

[0072] The organic branched chain R of POSS-(NH2)8 involved in the above process is: .

[0073] Polymerization of flame retardant and anti-drip nylon material: The difference from Comparative Example 1 is that POSS flame retardant and anti-drip salt: phosphorus flame retardant salt: nylon 66 salt = x:y:z, x=1, y=5, z=100, and the other conditions are the same as Comparative Example 1.

[0074] To demonstrate the practical effect of the present invention, the polymer materials prepared in the above embodiments and comparative examples were injection molded and subjected to a vertical combustion test according to ASTM D 3801. The sample size was 12.5 cm×1.3 cm×0.3 cm. The specific conditions are as follows.

[0075]

[0076] It can be seen from Table 1 that in Comparative Examples 1-3, as the amount of phosphorus flame retardant salt added increases, the damaged length of the material decreases, which proves that phosphorus has a certain flame retardant effect. However, when the amount of phosphorus flame retardant salt added is increased to phosphorus flame retardant salt: nylon 66 salt = 15:100, the material still cannot have anti-melting droplet ability, indicating that the anti-melting droplet ability of phosphorus flame retardant salt is limited.

[0077] Compared with Comparative Example 1, a small amount of POSS flame retardant and anti-melting dripping salt is added in Comparative Example 4. Although droplets will still be produced, it will not ignite the absorbent cotton, and the damage length is significantly reduced. This shows that the POSS flame retardant and anti-melting dripping salt can play a synergistic flame retardant and anti-melting dripping role with the phosphorus flame retardant salt.

[0078] Further increasing the amount of POSS flame retardant and anti-melting dripping salt added, Example 1 did not show the phenomenon of dripping during the UL-94 vertical combustion test. Compared with Example 1, Examples 2, 3, and 4 added phosphorus flame retardant salt and POSS flame retardant and anti-melting dripping salt, and it was found that the strips did not produce dripping, and the flame retardant properties were improved, as shown in detail. Figure 1 shown.

[0079] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A flame retardant and anti-melting dripping nylon material, obtained by polymerization reaction of POSS flame retardant and anti-melting dripping salt, phosphorus flame retardant salt and nylon salt; The molar ratio of the POSS flame retardant and anti-melting salt, the phosphorus flame retardant salt and the nylon salt is (3-10): (5-15): 100; The POSS flame retardant and anti-melting salt is obtained by reacting POSS-(NH2)8 with adipic acid in a molar ratio of 1:(2-8); The phosphorus flame retardant salt is obtained by reacting a phosphorus flame retardant with a nylon monomer at a molar ratio of 1:(0.5-2); The phosphorus-based flame retardant is selected from one or more of the following compounds: The nylon monomer is selected from hexamethylenediamine and / or adipic acid.

2. The flame retardant and anti-drip nylon material according to claim 1, characterized in that: The structure of the POSS-(NH2)8 is shown in Formula I: In formula I, R is an alkane or an aromatic hydrocarbon containing an amino group.

3. The flame retardant and anti-drip nylon material according to claim 1 or 2, characterized in that: The nylon salt is selected from one or more of nylon 66 salt, nylon 6 salt, nylon 56 salt, nylon 46 salt, nylon 610 salt, nylon 1010 salt and nylon 1212 salt.

4. The method for preparing the flame retardant and anti-drip nylon material according to any one of claims 1 to 3 comprises the following steps: S1, preparing POSS flame retardant anti-drip salt; S2, preparing phosphorus flame retardant salt; S3, mixing the POSS flame retardant and anti-melting dripping salt, the phosphorus flame retardant salt and the nylon salt, and reacting to obtain the flame retardant and anti-melting dripping nylon material.

5. A composite material, made from the flame retardant and anti-drip nylon material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Halogen-free molten-drop-resistant anti-flaming nylon-6 resin and preparation method

    CN107189061A

  • Preparation method of anti-molten-drop flame-retardant nylon material

    CN112239601A

  • Silicon / phosphorus synergistic flame-retardant polyamide resin

    CN112300570A